Mechanism of active component β-sitosterol from Myristica fragrans inducing apoptosis in bladder cancer cells via regulating the BCL-2/BAX/caspase-3 pathway - Zhu, Yongkang; Tang, Zhao; Lu, Zhaoyue; Gao, Dongyang; Pan, Hao; Jiang, Haozhe; Zhang, Zhen; Zhang, Huiqing (Frontiers in Oncology, 2025)
BackgroundNutmeg (Myristica fragrans) has been traditionally used in herbal medicine, but its potential anti-cancer effects remain largely unexplored. This study aimed to investigate the molecular mechanisms of nutmeg against bladder cancer through an integrated strategy combining network pharmacology, molecular docking, and in vitro validation.MethodsActive compounds of nutmeg were retrieved from the TCMSP and PubChem databases using oral bioavailability (OB ≥30%) and drug-likeness (DL ≥0.18) as criteria. Potential targets were predicted using SwissTargetPrediction and cross-referenced with bladder cancer-related genes from GeneCards, OMIM, and TTD. Common targets were analyzed by STRING, Cytoscape, and DAVID for PPI, GO, and KEGG enrichment. Molecular docking was performed to evaluate binding affinities between candidate compounds and core targets. In vitro experiments, including CCK-8, colony formation, wound-healing, Transwell, flow cytometry, and Western blotting, were conducted to validate the anti-tumor effects of β-sitosterol on T24 and 5637 bladder cancer cells.ResultsNine active compounds were identified, with β-sitosterol emerging as the key candidate. A total of 284 overlapping targets were obtained between nutmeg and bladder cancer. GO and KEGG enrichment suggested significant involvement in apoptosis and PI3K-Akt signaling pathways. Molecular docking showed that β-sitosterol exhibited strong binding to BCL-2 (–8.6 kcal/mol) and CASP3 (–8.3 kcal/mol). In vitro, β-sitosterol significantly reduced cell viability (IC50: 50 μM for 5637, 60 μM for T24), inhibited proliferation, colony formation, and migration, and induced apoptosis in a dose-dependent manner. Western blot confirmed upregulation of Bax and cleaved Caspase-3 and downregulation of BCL-2.ConclusionThis study demonstrates that β-sitosterol, a major bioactive compound of nutmeg, suppresses bladder cancer progression by modulating the BCL-2/Bax/Caspase-3 axis and PI3K-Akt signaling pathway. These findings provide novel insights into the therapeutic potential of nutmeg as a complementary strategy for bladder cancer treatment.